Early Efficacy of Multitiered Dual-Language Instruction: Promoting Preschoolers' Spanish and English Oral Language - Trina D. Spencer; Meghan Moran; Marilyn S. Thompson; Douglas B. Petersen; M. Adelaida Restrepo (SAGE Publishing, 2020)
The purpose of this cluster randomized group study was to investigate the effect of multitiered, dual-language instruction on children's oral language skills, including vocabulary, narrative retell, receptive and expressive language, and listening comprehension. The participants were 3- to 5-year-old children (n = 81) who were learning English and whose home language was Spanish. Across the school year, classroom teachers in the treatment group delivered large-group lessons in English to the whole class twice per week. For a Tier 2 intervention, the teachers delivered small-group lessons 4 days a week, alternating the language of intervention daily (first Spanish, then English). Group posttest differences were statistically significant, with moderate to large effect sizes favoring the treatment group on all the English proximal measures and on three of the four Spanish proximal measures. Treatment group advantages were observed on Spanish and English norm-referenced standardized measures of language (except vocabulary) and a distal measure of language comprehension.